The ex-ante aggregation of opinions under uncertainty - Leandro Nascimento (Theoretical Economics, 2012)
This paper presents an analysis of the problem of aggregating preference orderings under subjective uncertainty. Individual preferences, or opinions, agree on the ranking of risky prospects, but are quite general because we do not specify the perception of ambiguity or the attitude towards it. A convexity axiom for the ex-ante preference characterizes a (collective) decision rule that can be interpreted as a compromise between the utilitarian and the Rawlsian criteria. The former is characterized by the independence axiom as in Harsanyi (1955). Existing results are special cases of our representation theorems, which also allow us to interpret Segal's (1987) two-stage approach to ambiguity as the ex-ante aggregation of (Bayesian) future selves' opinions.
Keywords: D70; D81; 330; Aggregation of preferences; uncertainty